Social campaigns as a possibilities to build cooperation sports organizations with business organizations. Actions embedded in the CSR concept - Gabriel Pawlak; Anna Kulpaczyńska; Dawid Kutryn (Kazimierz Wielki University, 2017)
The aim of the article is to indicate the possibility of joint action in the strategic CSR-profit organizations (min. Company) and non-profit (min. Sports clubs). The authors point to social campaigns as one of the possibilities, which allows for the creation of joint business-social projects, with particular focus on the context of CSR and the 7th ISO 26000 area; the involvement and development of local communities.